PENINGKATAN KINERJA MELALUI PENGELOLAAN KEPUASAN KERJA: PERAN MOTIVASI DAN KOMPENSASI - Lia Juhriah Lukitawati; Dematria Pringgabayu (Politeknik Negeri Jakarta, 2018)
AbstractThe aims of research is to knoe the motivation, compensation, job satisfactions, and employee performance at Fakultas Ekonomi dan Bisnis Universitas Negeri. This research conducted at Fakultas Ekonomi dan Bisnis Universitas Negeri with cencus method in which sample used of is all employee of Fakultas Ekonomi dan Bisnis Universitas Negeri with totaling 73 people. The techniques of data conducted through questionnaires, interviews and observation and descriptive method of analysis with a quantitative approach.Variabels examined in this study was variable motivation, compensation, as the independent variable, job satisfaction as intervening variable and the variable performance of employee serves as the dependent variabel. As for hypothesis used path analysis and simple regression using a significance level of 0.05 with SPSS version 22 and Microsoft Excel 2013.Based on the results of the process and analysis of data in this study it can be concluded. Motivation well in the category with an average score of 3.89. For compensation quite well in the category with an average score of 2.90. For job satisfactions quite well in the category with an average score of 2.97. And Employee performances quite well in the category with an average of 3.13. In addition, from the processing and analysis of data in this study resulted in the following conclusions: 1) Motivation effect on satisfaction significantly 46.10%. 2) Compensation effect on satisfaction significantly 33.1%. 3) Motivation and compensation effect on teacher compensation sifnificantly 79.3% and 4) Teacher compensation effect of teacher performance significantly 86.8%.Keywords: Motivation, Compensation, Job satisfaction, Employee performanceAbstrakPenelitian ini bertujuan untuk mengetahui gambaran motivasi kerja, kompensasi, kepuasan kerja dan kinerja pegawai di Fakultas Ekonomi dan Bisnis Universitas Negeri. Selain itu penelitian ini bertujuan pula untuk mengetahui seberapa besar pengaruh motivasi kerja dan kompensasi pegawai terhadap peningkatan kepuasan kerja dan implikasinya terhadap kinerja pegawai di Fakultas Ekonomi dan Bisnis Universitas Negeri. Penelitian ini dilaksanakan di Fakultas Ekonomi dan Bisnis Universitas Negeri dengan metode sensus dimana sampel yang digunakan sejumlah populasi yaitu seluruh pegawai Fakultas Ekonomi dan Bisnis Universitas Negeri yang berjumlah 73 orang. Adapun teknik pengumpulan data dilakukan melalui angket, wawancara dan observasi langsung serta menggunakan metode analisis deskriptif dengan pendekatan kuantitatif.Hasil dari pengolahan dan analisis data dalam penelitian ini dapat disimpulkan bahwa Motivasi kerja berpengaruh terhadap kepuasan kerja pegawai sebesar 46,1%, kemudian kompensasi berpengaruh terhadap kepuasan pegawai sebesar 33,1%, motivasi kerja dan kompensasi berpengaruh terhadap kepuasan kerja pegawai sebesar 79,3% dan kepuasan kerja berpengaruh terhadap kinerja pegawai sebesar 86,8%Kata Kunci: kosakata bahasa Inggris teknik, perangkat lunak, mudah dibawa